2012
DOI: 10.5194/acp-12-2055-2012
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory investigation into the aggregation efficiency of small ice crystals

Abstract: Abstract. The aggregation of ice crystals and its temperature dependence is studied in the laboratory using a large ice cloud chamber. This process is important to the evolution of ice clouds in earth's atmosphere, yet there have been relatively few laboratory studies quantifying this parameter and its dependence on temperature. A detailed microphysical model is used to interpret the results from the experiments and derive best estimates for the aggregation efficiency as well as error bars. Our best estimates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 51 publications
(80 reference statements)
2
88
0
Order By: Relevance
“…Recently, Connolly et al (2012) showed that large aggregation efficiencies were associated with ice crystals that had quite complex geometry. In their study dendrites and stellar crystal habits had much higher aggregation efficiencies than simple hexagonal plates or columnar crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Connolly et al (2012) showed that large aggregation efficiencies were associated with ice crystals that had quite complex geometry. In their study dendrites and stellar crystal habits had much higher aggregation efficiencies than simple hexagonal plates or columnar crystals.…”
Section: Discussionmentioning
confidence: 99%
“…This was done in some former studies (see, e.g., Passarelli, 1978;Lin et al, 1983;Mitchell, 1988;Levkov et al, 1992;Ferrier, 1994;Lawson et al, 1998;Field and Heymsfield, 2003;Morrison et al, 2005). However, the main focus in all these model studies as well as in most observational studies (see, e.g., Field et al, 2006;Connolly et al, 2012) is on the "high" temperature regime, i.e. T > −30 • C, where precipitation is mainly formed via the ice phase.…”
Section: Introductionmentioning
confidence: 99%
“…The Manchester Ice Cloud Chamber (MICC) is a 10 m high stainless-steel tube of 1 m diameter which is contained in three cold rooms (spanning over three floors ;Connolly et al, 2012;Emersic et al, 2015). The cold rooms can be temperature-controlled from room temperature to approximately −50 • C. Two scroll pumps are used to evacuate the chamber in order to form clouds in these experiments.…”
Section: Manchester Ice Cloud Chamber (Micc)mentioning
confidence: 99%
“…The Aerosol-Cloud and Precipitation Interactions Model (ACPIM; Connolly et al, 2012) was chosen for testing of the experimental data of the ammonium sulfate control runs. The model is adapted to be used with chamber measurement data such as the ones reported here.…”
Section: Model Comparison For Ammonium Sulfate Control Experimentsmentioning
confidence: 99%